Bezen Perrot: The Breton nationalist unit of the SS, 1943-5 - (:unkn) unknown (My University, 2008)
This article charts the origins and course of the wartime Breton collaborationist force, the Bezen Perrot (Perrot Unit). For the first time in English, and employing source material previously unused in any language, it investigates the impact of the 'Irish example' upon Breton militancy from clandestine beginnings to military 'alliance' with Nazi Germany, with particular focus upon nationalist leader Célestin Lainé (aka 'Neven Henaff'). Employing primary material such as interviews with Bezen Perrot veterans and their descendants, previously unpublished photographs, and Lainé's own unpublished memoirs, the motivations of the Bezen's chief identities are contextualised within a Celtic nationalist framework. The article presents an anglophone readership with a largely unexplored chapter of Celtic history while simultaneously challenging much of the French historiography on this controversial subject.
Keywords: Brittany; Breton nationalism; collaboration; Bezen Perrot; French Resistance; Second World War; Irish inspiration; Célestin Lainé